Motivo de realizacao e desenvolvimiento economico - Angelini, Arrigo Leonardo; Bitencoürt Arrigoaco, Jose Fernando; Rosamilha, Nelson (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This study has as its objective the study of the achievement motivation and the level of economic development of an area. To this end, an evaluation was made, following the technique used by McClelland, of the achievement motive of adolescents who lived in regions characterized by different stages of industrialization.